Design and numerical modelling strategy to form Tailored Fibre Placement preforms: Application to the tetrahedral part with orthotropic final configuration. (July 2022) - Simon, J.; Hamila, N.; Binetruy, C.; Comas-Cardona, S.; Masseteau, B.
Abstract: Tailored Fibre Placement (TFP) allows manufacturing net shape preforms with continuously varying orientations and thickness. This additive technology, combined with forming, enables the design of fibre reinforced composite parts with optimized fibre orientations. A new modelling strategy to simulate the forming of thin dry TFP preform without backing material is proposed. The finite element model is based on an embedded element formulation, which assumes the stitching yarn to act as a bond between fibre tows of adjacent layers. Fibre tows are modelled with 2-node beam elements having independent generalized stress stiffnesses. The forming of a tetrahedral shape with orthotropic final configuration is addressed both experimentally and numerically to validate the proposed approach. The tetrahedral shape has a direct industrial application since it corresponds to corner brackets. This study also demonstrates the ability to improve the mechanical properties of engineered part using the hybrid TFP-forming process. Graphical abstract: Highlights: Hybridization of Tailored Fibre Placement and forming to manufacture 3D composite parts. Development of a tailor-made FE model to form Tailored Fibre Placement preforms. Experimental validation and numerical dry forming of an orthotropic tetrahedral part.